THE ROLE OF QUALITY METHODS IN IMPROVING EDUCATION PROCESS: CASE STUDY - Dragan Pavlović; Milena Todorović; Srđan Mladenović; Peđa Milosavljević (Serbian Journal of Management, 2014)
This paper presents a methodology for applying the Lean Six Sigma method on the educational process. After defining defects that have negative influence on the final quality evaluation of higher education and how these defects can be remedied, the Pareto analysis is done, and that is used for establishing a vital minority of the exams that are critical for examination of faculty. The next step is the Statistical Process Control (SPC) analysis that is performed on the exams that are classified as vital minority in Pareto analysis. Ishikawa diagram shows a relation between considered consequence (small number of passed exams) and all factors that influence this consequence. Based on the results of implementation of the Lean Six Sigma method in the educational process and implementation of all suggested improvements, the comparative overview of Pareto analysis is given for 2009/2010 and 2012/2013 academic year at the Faculty of Mechanical Engineering, University of Niš.